Point to point navigation a memoir, 1964 to 2006 - Vidal, Gore 1925-2012 (Doubleday, 2006)
"Celebrated novelist, essayist, critic, and controversialist Vidal ranges freely over his remarkable life with the signature wit and literary elegance that is uniquely his. From his desks in Ravello and the Hollywood Hills, Gore Vidal travels in memory through the arenas of literature, television, film, theater, politics, and international society, where he has cut a broad swath, recounting achievements and defeats, friends and enemies made and lost. Among the gathering of notables to be found in these pages are Jack and Jacqueline Kennedy, Tennessee Williams ("the Glorious Bird"), Eleanor Roosevelt, Orson Welles, Johnny Carson, Greta Garbo, Federico Fellini, Rudolph Nureyev, Elia Kazan, and Francis Ford Coppola. Some of the book's most moving pages are devoted to the illness and death of his partner of five decades, Howard Austen, and indeed the book is, among other things, a meditation on mortality written in the spirit of Montaigne.--From publisher description."--From source other than the Library of Congress